Karakteristik nanopartikel ekstrak teh hijau dengan metode nano milling dan nano spray - Shabri Shabri; Dr. Dadan Rohdiana; Hilman Maulana; Sugeng Haryanto; Muhammad Iqbal Prawira-Atmaja; Rachmat Mauludin; Muhammad Insanu; Asep W. Perdana (Research Institute for Tea and Cinchona, 2018)
Nanoparticles for raw materials of phytopharmaca is a technology used to be able to increase the effectiveness and efficiency of phytopharmaca in its absorption as a therapeutic agent. This study useds steamed green tea polyphenol extract as raw material with two nanoparticle methods, first nano milling by Planetary Ball Milling (PBM) and the second using encapsulation method with Nano Spray Dryer (NSD). The characteristics of nanoparticles were then analyzed using Particle Size Analyzer (PSA) and X-Ray Difraction (XRD) to determine the size, size distribution, and type of crystals formed by the two methods. The results of PBM had not been able to meet the criteria for nanoparticles because they had a particle size that is >1 µm, whereas the NSD method produced 554.7 nm nanoparticles with an intensity of 86.9%. And the results of the XRD analysis showed that the two methods of making nanoparticles resulted in amorphous particles >50%.